Pengaruh Model Process Oriented Guided Inquiry Learning (POGIL) Terhadap Hasil Belajar Siswa Pada Materi Titrasi Asam Basa Di SMA Negeri 1 Kakas Kabupaten Minahasa - Ratih Anita Memah; Sanusi Gugule; Dokri Gumolung (Oxygenius Journal Of Chemistry Education, 2020)
This study aims to determine the effect of POGIL learning models on student learning outcomes on acid-base titration subject. This research was conducted in class XI MIPA 2 and XI MIPA 3 in SMA Negeri 1 Kakas. The method used is an experimental method with a post-test only control design research design. The research sample consisted of 30 students, who were randomly drawn. The experimental class uses the POGIL method, the control class uses conventional learning. Student learning outcomes data obtained from post-test scores. Analysis of research data shows that there are differences in the average value of student learning outcomes of the experimental class taught by using the POGIL method and the average value of the learning outcomes of control class students who are taught by using conventional learning on mole concept material. Data analysis using t-test at a significant level α = 0.05. Statistical analysis of student learning outcomes obtained tcount > ttable or 3,078 > 2,048. So it can be concluded that there is a positive influence between student learning outcomes using the POGIL method and student learning outcomes using conventional learning on acid-base titration subject.